Variasi Sinar Ultraviolet pada Sistem Membran Ultrafiltrasi untuk Pengolahan Air Gambut - Erna Yuliwati; Edisfha Ajeng Rahayu; Heni Yuniar (LPPM Politeknik Jambi, 2022)
Abstract- Peat water treatment still has many obstacles, one of the alternatives that can be used to overcome this obstacle is membrane technology and UV light variais. This study aims to determine the effect of UV rays on the flux and content of BOD, TSS, pH, Turbidity, Color and E.Coli Bacteria. This study used a combined method, namely ultraviolet (UV) light poses using a UV Water Sterilizer, the filtration process using the KUF-3 ultrafiltration membrane and the phytoremediation method with kiambang plants. The results of this study showed the highest removal rate of BOD in the filtration process with UV 6 watts at 90 minutes of filtration time with an efficiency of 94.71%. The color removal rate in the filtration process with UV is 6 watts at 90 minutes of filtration time with an efficiency of 70.92%. Turbidity removal rate in the filtration process with UV 6 watts at 90 minutes filtration time with an efficiency of 99.97%%. The TSS removal rate in the filtration process with UV is 6 watts at 90 minutes of filtration time with an efficiency of 47.77%. The pH removal rate in the filtration process with UV is 6 watts at 90 minutes of filtration time with an efficiency of 24.79%. The elimination rate of E.coli bacteria in the filtration process with UV is 6 watts at 90 minutes of filtration time with 100% efficiency.